Implementasi Aplikasi Sara Terhadap Produktivitas Karyawan Engineering Di Hotel Pullman Dan Ibis Bandung - Felicia Della Raharja; Chandra Hendriyani; Tengku s Rochmah (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
The COVID-19 pandemic which has an impact on the establishment of the Work from Home (WFH) work system from Work from Office (WFO). The agility of the Pullman Hotel and Ibis Bandung Grand Central companies in responding to pandemic conditions by utilizing technology is carried out through the SARA Hotel Operation application which is used to facilitate the work of employees in receiving complaints, especially to the engineering department from guests and from other departments. The engineering department previously used the Work Order form to receive complaints from external or internal. Many Work Order forms are not archived properly so that the Head of the Engineering Department and the Chief Engineering find it difficult to report to the Hotel Manager or to the General Manager. The research methodology used is descriptive qualitative method with data collection techniques of observation, interviews, and literature study. The results showed that the SARA application increased work productivity, especially indicators of effectiveness. The SARA application is also useful for employees, engineering department teams and leaders for monitoring and making real time work reports.